Church in an Age of Global Migration A Moving Body - Snyder, Susanna; Ralston, Joshua; Brazal, Agnes M.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This volume examines the ways in which migrants and the phenomenon of migration expose longstanding gaps and failings within Christian communities but also open up fresh possibilities for churches to grow and diversify.
Keywords: Science; Science; Science, general; Electronic books